نمـــــــوذج تصميمــــــي لتأســـــيســـــات الميـــــاه في الأبنيــــة - خلـــــف الجـميلـــــي, كــــــريم (Journal of Engineering and Sustainable Development, 2005)
Water installations in buildings are of great importance in the essence of direct relationship between potable water and public health, as well as, with daily life activities of residents. Even though, design and execution of water installations in houses and multistory buildings remain systematic.In this research, a new approach of analysis and design could be useful for water installation in buildings and residential houses have been developed. This approach is based on the idea of feeding the elevated tanks and all fixtures, inside the building, simultaneously by only one up-feed /down-feed pipe instead of two or three pipes which are ordinarily used .The proposed approach is not only economical but also enabling the consumers to be supplied with hygienically safe water.Hydraulic analysis have been carried out for both, houses and buildings installations. To check the applicability of the system, a prototype has been installed, operated and tested for a single floor house, through, which a good agreement has been shown between analytical and observed results.